The characterization of thermoplastic starch (TPS) reinforced with banana peel (BP) Polymer composites - Huzaisham, Nur Athirah (2021)
This study presents the characterization of thermoplastic starch (TPS) reinforced with banana peel (BP) polymer composites. Recently, various studies have centred more on the use of polymer composite where thermoplastic starch (TPS) has received significant attention to behave as the composite matrix due to its degradable nature. In the meantime, numerous types of fillers especially from natural and renewable resources such as biomass and agricultural waste have also been considered. This is important to guarantee the sustainability of our environment and to overcome the high demand for plastics generated by crude oil and natural gas where the supply is minimal. Since most of the previous studies more focusing on the usage of starch/polyester, starch/PVA and starch/PLA blends, this research is motivated to fabricate biodegradable polymer composite derived from starch/biomass blend. The research aims to formulate TPS/BP polymer composites under different concentration of BP as well as to evaluate the mechanical and physical properties of the TPS/BP polymer composites. The preparation of samples involved several stages where the BP were extracted via maceration method and subsequently integrated into the TPS matrix to form TPS/BP polymer composite. In this study, it is apparent that the sample with 10 wt.% of BP withstand the highest tensile strength and tear resistance up to 39.303 MPa and 66.388 N/mm, respectively. In terms of biodegradability, it can be concluded that composites with 40 wt.% of BP exhibited higher degradation rate of 65.1% average weight loss as compared to 5 wt.% of BP with only 45.2% average weight loss within eight weeks. Evidently, TPS/BP polymer composites demonstrated considerably good physical and mechanical performance as an alternative to the existing biodegradable polymer.